Helena Antipoff e o ensino na capital mineira: a Fazenda do Rosário e a educação pelo trabalho dos meninos "excepcionais" de 1940 a 1948 - Rafante, Heulalia Charalo (2006)
Rosário Farm was founded in 1940 by Russian educator Helena Antipoff as a boarding school for receiving exceptional children from Belo Horizonte. Our study analyzed the pedagogical practices of that institution, verifying how those attitudes reflected in inmates life. First, we introduce Antipoff s path, understanding her educational principles as well as her motivations to come to Brazil in 1929. After that, we follow her performance next to teaching system of Minas Gerais capital in 1930 s, and her path during the creation of institutions for educating children as she called exceptional , including of Rosário Farm. Finally, based on learning the Rosário Farm history, we examine children profile, the pedagogical actions, the course of inmates, their reactions to institutionalizing process, testifying the work became the thread of those relations. After a study of adopted work conditions as educative principle, we weave a review of the way of teaching and performance junction happened in the institution.